A summary of the investigation report on the Tianjiayi explosion incident (21 March 2019). Issue 1 (14th January 2020) - You, Zuoling; Yu, Jing; Liu, Ying; Zhang, Yunrui; Zhang, Bo
Abstract: A severe explosion occurred on 21 March 2019 at Tianjiayi Chemical Co., Ltd, located in the Xiangshui Eco‐chemical Industrial Park, Jiangsu Province, China, which resulted in 78 deaths, 76 serious injuries, and 640 minor injuries. The explosion caused direct economic losses of RMB 1.98 billion yuan. A summary of the incident investigation report is presented. One direct outcome of the accident was the accumulation of heat in solid waste, which resulted in a temperature increase beyond autoignition temperature, while the indirect root‐causes included deficient safety management, inadequate supervision, lack of safety awareness and other factors. In addition, the administrative and criminal liabilities of responsible personnel and inadequacy of prevention measures is summarized.